Dustproof cover and head-up display device comprising same

The dust cover design with specific support plates and iodine-based polarizer minimizes warping and polyene formation, ensuring effective heat insulation and display performance in head-up display devices.

CN119200230APending Publication Date: 2024-12-27NITTO DENKO CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410834603.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-04-19
Filing Date
2024-06-26
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Iodine-based polarizers in head-up display devices are prone to warping and polyene formation due to high temperatures, which degrade display performance, particularly in vehicle-mounted applications.

Method used

A dust cover design incorporating a first and second support plate with specific moisture permeability and thickness, along with an iodine-based polarizer, where the distance between the center lines of the polarizer and dust cover is minimized to suppress warping and polyene formation.

Benefits of technology

The design effectively reduces warping and polyene formation, maintaining display performance and enhancing heat insulation properties, even under high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119200230A_ABST
    Figure CN119200230A_ABST
Patent Text Reader

Abstract

Provided is a dust cover in which warpage of the dust cover is suppressed, and in which polyene formation of a polarizer can be suppressed even when an iodine-based polarizer is used. The dust cover is a dust cover including a first support plate, a polarizing plate including an iodine-based polarizer, and a second support plate, the moisture permeability of at least one of the first support plate or the second support plate being 37 g / (m < 2 >. 24 hours) or more, and the thickness of at least one of the first support plate or the second support plate being 200 [mu] m or more. The distance between the center line LP of the iodine-based polarizer in the thickness direction thereof and the center line LD of the dust cap in the thickness direction thereof is 20 [mu] m or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a dustproof cover and a head-up display device comprising the dustproof cover. Background Art

[0002] Head-up display devices have begun to be developed and put into practical use. In the head-up display device, a dust cover covering the opening portion of the optical path is arranged to prevent foreign matter such as dust from entering a housing storing a display or the like. In addition, for example, it has been proposed to bond a polarizing plate to the dust cover to prevent the temperature in the housing from rising due to the incidence of sunlight (for example, WO2017 / 199916 A1). Summary of the invention

[0003] Iodine-based polarizers and dye-based polarizers are generally referred to as polarizers. The iodine-based polarizer can provide a dust cover with higher heat insulation properties because its polarization degree can be higher than that of the dye-based polarizer. At the same time, due to high temperature, the iodine-based polarizer is prone to cause polyene formation and warping (for example, warping of the dust cover), so the display performance of the head-up display device may be reduced. Therefore, the following dust cover is needed: the dust cover is suppressed from warping, and even when the iodine-based polarizer is used, the dust cover can suppress the polyene formation of the polarizer.

[0004] 1. According to at least one embodiment of the present invention, there is provided a dust cover comprising: a first support plate; a polarizing plate comprising an iodine-based polarizer; and a second support plate, wherein the moisture permeability of at least one of the first support plate or the second support plate is 37 g / (m 2 · 24 hours) or more, the thickness of at least one of the first support plate or the second support plate is 200 μm or more, wherein the center line L of the iodine-based polarizer in the thickness direction thereof P and the center line L of the dust cover in its thickness direction D The distance between them is 20 μm or less.

[0005] 2. According to at least one embodiment of the present invention, there is provided a dust cover comprising: a first support plate; a polarizing plate comprising an iodine-based polarizer; and a second support plate, wherein the moisture permeability of at least one of the first support plate or the second support plate is 37 g / (m 2 · 24 hours) or more, at least one of the first support plate or the second support plate has a tensile elastic modulus of 1,600 MPa or more, which is measured at 23°C ± 2°C, wherein the iodine-based polarizer has a center line L in the thickness direction thereof P The center line L of the dust cover in its thickness direction D The distance between them is 20 μm or less.

[0006] 3. In the dust cover according to item 1 or 2 above, the support plate may include a base material and a surface resin layer.

[0007] 4. In the dust cover according to the above item 3, the base material may contain a polycarbonate-based resin.

[0008] 5. In the dust cover according to item 3 or 4 above, the surface resin layer may contain polymethyl methacrylate.

[0009] 6. In the dustproof cap according to any one of items 3 to 5 above, the thickness of the surface resin layer may be 30 μm or more.

[0010] 7. In the dust cover according to any one of items 1 to 6 above, the iodine content of the polarizer may be 2.2 wt % to 4.0 wt %.

[0011] 8. According to at least one embodiment of the present invention, there is provided a head-up display device, comprising: a display configured to emit projection light; at least one reflector configured to reflect the projection light; and a dust cover according to any one of items 1 to 7 above. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 is a schematic cross-sectional view of a dust cover according to at least one embodiment of the present invention.

[0013] Figure 2 is a schematic cross-sectional view of a head-up display device according to at least one embodiment of the present invention. DETAILED DESCRIPTION

[0014] Embodiments of the present invention are described below. However, the present invention is not limited to these embodiments.

[0015] A. Overall configuration of dust cover

[0016] Figure 1is a schematic cross-sectional view of a dust cover according to at least one embodiment of the present invention. The dust cover 100 of the illustrated embodiment includes: a first support plate 20; a polarizing plate 10 including an iodine-based polarizer 11; and a second support plate 20'. The first support plate 20 and the second support plate 20' may be the same support plate, or may be different support plates. In at least one embodiment of the present invention, the first support plate 20 and the second support plate 20' preferably include substrates 21 and 21', and surface resin layers 22 and 22'. The polarizing plate 10 generally includes an iodine-based polarizer 11 and protective layers 12 and 13 arranged on both sides of the polarizer 11. The polarizing plate 10 may also include any other suitable layer in addition to the protective layer. Other layers are, for example, a delay layer. The various components of the dust cover may be laminated via any suitable adhesive layer (not shown). Specific examples of adhesive layers include adhesive layers and pressure-sensitive adhesive layers. In the illustrated embodiment, the first support plate 20 and the polarizing plate 10 are laminated via a first pressure-sensitive adhesive layer 30. In addition, the polarizing plate 10 and the second supporting plate 20' are laminated via the second pressure-sensitive adhesive layer 30'. In the dust cover 100, the center line L of the iodine-based polarizing plate 11 in the thickness direction thereof is P The center line L of the dust cover 100 in the thickness direction D The distance between L is 20 μm or less. P and L D Overlap with each other. At least one of the first support plate 20 or the second support plate 20' has a thickness of 200 μm or more. In the illustrated embodiment, the thickness of the first support plate 20 and the second support plate 20' are both 200 μm or more. The thickness of the first support plate 20 and the second support plate 20' may be the same or different from each other. In addition, the moisture permeability of at least one of the first support plate 20 or the second support plate 20' is 37 g / (m 2· 24 hours) or greater. The moisture permeability of the first support plate 20 and the second support plate 20 'may be the same or different from each other. The polarization degree of the iodine-based polarizer is higher than the polarization degree of the dye-based polarizer, and the heat insulation property is higher than the heat insulation property of the dye-based polarizer, so the damage caused by sunlight to the inside of the head-up display device (e.g., image display device) can be further reduced. At the same time, in the dust cover using the iodine-based polarizer, the warping of the dust cover and the polyene formation of the polarizer become problems, and as a result, the display performance of the head-up display device to which the dust cover has been applied may be reduced. In particular, in a vehicle-mounted head-up display device, such a problem may be significant because the device may be placed in an environment with a higher temperature. According to the dust cover of at least one embodiment of the present invention, the following dust cover can be obtained: the dust cover is suppressed from warping, and even when an iodine-based polarizer is used, the dust cover can also suppress the polyene formation of the polarizer. As a result, even when the dust cover is used for a vehicle-mounted head-up display device, the damage caused by sunlight to the inside of the head-up display device can be further reduced.

[0017] As described above, in the dust cover according to at least one embodiment of the present invention, the center line L of the iodine-based polarizing plate 11 in the thickness direction is P The center line L of the dust cover 100 in the thickness direction D The distance between them is 20 μm or less. P With L D The distance between L is preferably 18 μm or less, more preferably 15 μm or less, and still more preferably 10 μm or less. P With L D The distance between the center line L and the center line L of the iodine-based polarizing plate 11 in the thickness direction is preferably as small as possible and may be 0 μm. P The center line L of the dust cover 100 in the thickness direction D can be in the same position. P With L D When the distance between the dust cover and the dustproof cover falls within the above range, warping of the dustproof cover can be further suppressed.

[0018] The thickness of the dust cover can be set to any appropriate value. The thickness of the dust cover is preferably 300 μm to 750 μm, more preferably 350 μm to 700 μm, still more preferably 400 μm to 650 μm, and particularly preferably 450 μm to 600 μm. When the thickness of the dust cover falls within the above range, a dust cover having excellent dustproof and heat-insulating properties can be obtained.

[0019] The dust cover 100 is generally transparent. The term "transparent" as used herein means that the dust cover has the property of transmitting visible light with a wavelength of 360nm to 830nm. The term "transparent" includes: the case where the dust cover does not absorb substantially visible light and transmits light of any wavelength in the visible light region (colorless and transparent); and the case where the dust cover absorbs light beams of some wavelengths in the visible light region and transmits light of wavelengths other than these wavelengths (colored and transparent). The dust cover is preferably colorless and transparent. The total light transmittance of the dust cover is preferably 50% or more, more preferably 70% or more, and even more preferably 90% or more. The total light transmittance is a value measured in accordance with JIS K 7375.

[0020] The surface shape of the dust cover 100 can be designed into any suitable shape according to the shape of the opening portion of the head-up display device to which the dust cover is applied. For example, the portion of the dust cover covering the opening portion may include only a flat surface or only a curved surface, or the portion covering the opening portion may include multiple flat surfaces and / or multiple curved surfaces. Generally, the surface shape of the dust cover may include only a flat surface or only a curved surface.

[0021] The components of the dust cover are described in more detail below.

[0022] B. Support plate

[0023] The first support plate 20 and the second support plate 20' (hereinafter also referred to as "support plates") may be arranged on both sides of the polarizing plate 10. The first support plate 20 and the second support plate 20' may be the same support plate, or may be different support plates. The moisture permeability of at least one of the first support plate 20 or the second support plate 20' is 37 g / (m 2 · 24 hours) or more. The moisture permeability of each of the support plates is 37 g / (m 2 ·24 hours) or more, preferably 40g / (m 2 ·24 hours) or more, more preferably 45g / (m 2 ·24 hours) or more, still more preferably 50g / (m 2 · 24 hours) or more. The moisture permeability of each of the support plates is, for example, 70 g / (m 2 · 24 hours) or less. When the moisture permeability of each of the support plates falls within the above range, the following dust cover can be obtained: the dust cover is suppressed from warping, and even when an iodine-based polarizing plate is used, the dust cover can suppress polyene formation of the polarizing plate. As used herein, the term "moisture permeability" refers to a value measured under the conditions of a temperature of 40° C. and a humidity of 92% RH according to JIS Z 0208.

[0024] In at least one embodiment of the present invention, the thickness of at least one of the first support plate 20 or the second support plate 20' is 200 μm or greater. The thickness of each of the support plates is 200 μm or greater, preferably 220 μm or greater, and more preferably 250 μm or greater. In addition, the thickness of each of the support plates is preferably 300 μm or less. When the thickness falls within the above range, the following dust cover can be obtained: the dust cover is suppressed from warping, and even when an iodine-based polarizer is used, the dust cover can suppress the polyene formation of the polarizer. In at least one embodiment of the present invention, the thickness of each of the support plates can be, for example, less than 200 μm, and is preferably 100 μm to 150 μm. In the above L P With L D When the distance between them is small (eg, 0 μm), warping is suppressed even when the thickness of each of the support plates is less than 200 μm, and polyene formation of the polarizer can be suppressed even when an iodine-based polarizer is used.

[0025] In at least one embodiment of the present invention, the tensile elastic modulus of each of the first support plate 20 and the second support plate 20' measured at 23°C ± 2°C is 1,600MPa or greater. The tensile elastic modulus of each of the support plates measured at 23°C ± 2°C is 1,600MPa or greater, preferably 1,700MPa or greater, more preferably 1,800MPa or greater, still more preferably 1,900MPa or greater, and particularly preferably 1,950MPa or greater. The tensile elastic modulus of each of the support plates measured at 23°C ± 2°C is preferably 3,000MPa or less. When the tensile elastic modulus of each of the support plates measured at 23°C ± 2°C falls within the above range, the following dust cover can be provided: the dust cover is suppressed from warping, and even when an iodine-based polarizer is used, the dust cover can suppress the polyene formation of the polarizer. In the present specification, the tensile elastic modulus of each of the support plates may be measured according to JIS K 7161 under the conditions of a temperature of 23° C.±2° C. and a humidity of 50% RH±10% RH.

[0026] Each of the support plates only needs to have a 2· 24 hours) or more moisture permeability, and can be formed by any suitable material. The material is, for example, a resin. Specific examples of resins include: ester-based resins, such as polyethylene terephthalate and polyethylene naphthalate; cellulose-based resins, such as diacetyl cellulose and triacetyl cellulose; polycarbonate-based resins, such as bisphenol A-based polycarbonate; acrylic resins, such as polymethyl methacrylate and lactone-modified acrylic resins; styrene-based resins, such as polystyrene and acrylonitrile-styrene copolymers; olefin-based resins, such as polyethylene, polypropylene, polyolefins with a cyclic structure or a norbornene structure, and ethylene-propylene copolymers; vinyl chloride-based resins; amide-based resins, such as aromatic polyamides; imide-based resins; sulfone-based resins; polyethersulfone-based resins; polyetheretherketone-based resins; polyphenylene sulfide-based resins; vinyl alcohol-based resins; vinylidene chloride-based resins; vinyl butyral-based resins; arylate-based resins; polyoxymethylene-based resins; and epoxy-based resins. Among them, polycarbonate-based resins are preferably used. The use of polycarbonate-based resins can provide a support plate excellent in transparency, impact resistance, heat resistance, durability, and bending processability. These resins can be used alone or in combination.

[0027] In at least one embodiment of the present invention, the support plates each include a substrate and a surface resin layer. Using support plates each including a substrate and a surface resin layer can provide a dust cover, which further improves heat resistance, further suppresses warping, and can further suppress polyene formation of the polarizer.

[0028] B-1. Base material

[0029] The base material of each of the support plates can be formed of any suitable material. For example, a resin can be used, and specifically, the resins given as examples of the resins for forming each of the above-mentioned support plates can be used. It is preferred to use a polycarbonate-based resin as the material for forming the base material. The use of a polycarbonate-based resin can provide a support plate with excellent transparency, impact resistance, heat resistance, durability and bending processability. These resins can be used alone or in combination.

[0030] The thickness direction retardation Rth(550) of the substrate is preferably 50 nm or less, more preferably 20 nm or less, still more preferably 10 nm or less, and particularly preferably 0 nm to 5 nm. When Rth(550) falls within the above range, the dust cover can be appropriately used as a dust cover for a head-up display. In this specification, the thickness direction retardation "Rth(λ)" refers to the thickness direction retardation measured at 23°C with light having a wavelength of λnm. Therefore, the term "Rth(550)" refers to the thickness direction retardation measured at 23°C with light having a wavelength of 550 nm. When the thickness of the layer (film) is expressed as "d" (nm), Rth(λ) is determined by the equation "Rth(λ)=(nx–nz)×d", where "nx" represents the refractive index in the direction in which the refractive index in the plane of the layer becomes the maximum (ie, the slow axis direction), and "ny" represents the refractive index in the direction perpendicular to the slow axis in the plane (ie, the fast axis direction).

[0031] The thickness of the substrate can be set to any appropriate thickness. The thickness of the substrate is preferably 100 μm to 270 μm, more preferably 170 μm to 265 μm. When the thickness of the substrate falls within the above range, a dust cover can be provided: the dust cover is suppressed from warping, and even when an iodine-based polarizing plate is used, the dust cover can suppress polyene formation of the polarizing plate.

[0032] In addition to the above resins, the substrate may contain any suitable additives. Examples thereof include infrared absorbers, UV absorbers, and flame retardant stabilizers. These additives may be used alone or in combination.

[0033] B-2. Surface resin layer

[0034] The formation of the surface resin layer can further improve the heat resistance of, for example, the dust cover. The surface resin layer can be formed of any suitable resin. Examples of resins include: (meth) acrylic resins, such as polymethyl methacrylate (PMMA); styrene-(meth) acrylic ester copolymer resins; hydrogenated styrene-(meth) acrylic ester copolymer resins (the benzene rings of the styrene component are made partially alicyclic by hydrogenation); aromatic polycarbonate resins copolymerized with 2,2-(4-hydroxy-3-methylphenyl) alkane; and compositions comprising (meth) acrylic resins copolymerized with (meth) acrylic monomers having aromatic rings and aromatic polycarbonate resins, the (meth) acrylic resins being compatible with the aromatic polycarbonate resins. Among them, (meth) acrylic resins and (meth) acrylic resins and hydrogenated styrene-(meth) acrylic ester copolymer resins (the benzene rings of the styrene component are made partially alicyclic by hydrogenation), and PMMA is more preferably used. When the surface resin layer is formed of such a resin, the following dust cover can be provided: the heat resistance of the dust cover is improved; in addition, the dust cover is further suppressed from warping, and even when an iodine-based polarizing plate is used, the dust cover can suppress polyene formation of the polarizing plate. In addition, a dust cover with low birefringence and excellent wear resistance can be provided. The term "(meth) acrylic acid" as used herein refers to acrylic acid and / or methacrylic acid.

[0035] The thickness of the surface resin layer is preferably 15 μm or more, more preferably 20 μm or more, further preferably 25 μm or more, and particularly preferably 30 μm or more. The thickness of the surface resin layer is preferably 60 μm or less. When the thickness of the surface resin layer falls within the above range, a dust cover that further suppresses warping can be provided.

[0036] The surface resin layer may contain any suitable additives other than the above resins. Examples thereof include infrared absorbers, UV absorbers, and flame retardant stabilizers. These additives may be used alone or in combination.

[0037] C. Polarizing plate

[0038] The polarizing plate 10 generally includes an iodine-based polarizer 11 and protective layers 12 and 13 arranged on both sides of the iodine-based polarizer 11. In at least one embodiment of the present invention, the absorption axis direction of the polarizing plate 10 (substantially an iodine-based polarizer 11) is generally set to be substantially parallel to the polarization direction of the projection light (generally linear polarized light) of the head-up display device using a dust cover. The expressions "substantially parallel" and "approximately parallel" as used herein both include the case where the angle formed between the two directions is 0°±7°, and the angle is preferably 0°±5°, and more preferably 0°±3°. The expressions "substantially perpendicular" and "approximately perpendicular" both include the case where the angle formed between the two directions is 90°±7°, and the angle is preferably 90°±5°, and more preferably 90°±3°. In addition, the simple expressions "perpendicular" or "parallel" as used herein may include a state where two directions are substantially perpendicular or substantially parallel to each other.

[0039] C-1. Polarizer

[0040] Iodine-based polaroids generally include resin films containing iodine as dichroic substances. Any suitable resin film that can be used as a polaroid can be used as the resin film. The resin film is typically a polyvinyl alcohol-based resin (hereinafter referred to as "PVA-based resin") film. The resin film can be a single-layer resin film, or can be a laminate of two or more layers.

[0041] Specifically, the polarizer including the monolayer resin film is a polarizer obtained by dyeing and stretching (usually uniaxial stretching) the PVA-based resin film with iodine. The above-mentioned dyeing with iodine is carried out by, for example, immersing the PVA-based resin film in an iodine aqueous solution. The stretching ratio of the above-mentioned uniaxial stretching is preferably 3 to 7 times. Stretching can be carried out after the dyeing process, or can be carried out while dyeing. In addition, dyeing can be carried out after stretching. The PVA-based resin film is subjected to, for example, swelling treatment, cross-linking treatment, washing treatment or drying treatment as required. For example, when washing with water by immersing the PVA-based resin film in water before dyeing, the pollution and anti-blocking agent on the surface of the PVA-based resin film can be washed off. In addition, the PVA-based resin film can swell to prevent uneven dyeing, etc.

[0042] Specifically, the polarizer obtained by using a laminate is a polarizer obtained, for example, by using: a laminate of a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate; or a laminate of a resin substrate and a PVA-based resin layer formed by applying on a resin substrate. The polarizer obtained by using a laminate of a resin substrate and a PVA-based resin layer formed by applying on a resin substrate can be produced, for example, by the following steps: applying a PVA-based resin solution to a resin substrate; drying the solution to form a PVA-based resin layer on a resin substrate, thereby providing a laminate of a resin substrate and a PVA-based resin layer; and stretching and dyeing the laminate to convert the PVA-based resin layer into a polarizer. In at least one embodiment of the present invention, a polyvinyl alcohol-based resin layer containing a halide and a polyvinyl alcohol-based resin is preferably formed on one side of the resin substrate. Stretching generally includes immersing the laminate in a boric acid aqueous solution to stretch the laminate. In addition, stretching may also include, as required, stretching the laminate in air at a high temperature (e.g., 95° C. or higher) before stretching in a boric acid aqueous solution. In addition, in at least one embodiment of the present invention, it is preferred that the laminate is subjected to a drying shrinkage treatment, wherein the laminate is shrunk by 2% or more in its width direction by conveying in its length direction while heating. The production method according to at least one embodiment of the present invention generally includes subjecting the laminate to an auxiliary stretching treatment in air, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment in the order described. When the auxiliary stretching is introduced, the crystallinity of the PVA can be improved even when the PVA is applied to the thermoplastic resin, and thus high optical characteristics can be achieved. In addition, at the same time, when the orientation characteristics of the PVA are improved in advance, problems such as the reduction of the orientation characteristics of the PVA and its dissolution when the PVA is immersed in water in the subsequent dyeing step or the stretching step can be prevented, and thus high optical characteristics can be achieved. In addition, in the case of immersing the PVA-based resin layer in a liquid, the orientation disorder of the polyvinyl alcohol molecules and the reduction of their orientation characteristics can be suppressed compared to the case where the PVA-based resin layer does not contain any halide. Thus, the optical characteristics of the polarizer obtained by the processing steps (such as dyeing and underwater stretching) carried out by immersing the laminate in a liquid can be improved. In addition, when the laminate is shrunk in its width direction by drying shrinkage treatment, its optical characteristics can be improved. The laminate of the obtained resin substrate and polaroid can be used as it is (that is, the resin substrate can be used as a protective layer of the polaroid), or can be used after the following steps: the resin substrate is peeled off from the laminate of the resin substrate and the polaroid, and any suitable protective layer according to the purpose is laminated on the peeled surface.Details of such a method of producing a polarizing plate are described in, for example, Japanese Patent Application Laid-Open No. 2012-73580 (Japanese Patent No. 5,414,738) and Japanese Patent No. 6,470,455, the descriptions of which are incorporated herein by reference in their entirety.

[0043] The iodine content of the polaroid is preferably 2 wt % or greater, more preferably 2 wt % to 10 wt %. Even when the iodine content of the polaroid falls within such a range, the dust cover according to at least one embodiment of the present invention can also suppress the formation of polyenes in the polaroid. As used herein, the term "iodine content" refers to the amount of all iodine molecules in the polaroid (PVA-based resin film). More specifically, in the polaroid, iodine is present in the form of, for example, iodide ions (I – ), iodine molecules (I2) or polyiodide ions (I3 – or I5 – ) forms, and the term "iodine content" as used herein refers to the amount of iodine including all these forms. The iodine content can be calculated by, for example, a calibration curve method of fluorescent X-ray analysis. The polyiodide ions exist in a state of forming a PVA-iodine complex in a polarizer. The formation of such a complex can exhibit absorption dichroism in the visible light wavelength range. Specifically, the complex of PVA and triiodide ion (PVA·I3 – ) has a light absorption peak at about 470 nm, and the complex of PVA and pentaiodide ion (PVA·I5 – ) has a light absorption peak at about 600 nm. As a result, polyiodide ions can absorb light in a wide visible light range depending on their form. – ) has a light absorption peak at about 230 nm, and therefore is not substantially involved in the absorption of visible light. Therefore, the polyiodide ions present in a state of complexing with PVA may be mainly involved in the absorption performance of the polarizer.

[0044] The thickness of the polarizing plate is preferably 1 μm to 30 μm, more preferably 1 μm to 25 μm, and still more preferably 1 μm to 20 μm. When the thickness of the polarizing plate falls within the above range, a dust cover having higher heat shielding properties can be provided.

[0045] The polarizer preferably exhibits absorption dichroism at any wavelength within the wavelength range of 380nm to 780nm. The single-layer transmittance Ts of the polarizer is preferably 40% to 48%, more preferably 41% to 46%. The polarization degree P of the polarizer is preferably 97.0% or greater, more preferably 99.0% or greater, and even more preferably 99.9% or greater. The above-mentioned single-layer transmittance is generally a Y value measured with a UV-visible spectrophotometer and calibrated for visibility. The above-mentioned polarization degree is generally determined by the following equation based on the parallel transmittance Tp and the cross transmittance Tc, which have been measured with a UV-visible spectrophotometer and calibrated for visibility.

[0046] Polarization degree (%) = {(Tp – Tc) / (Tp + Tc)} 1 / 2 ×100

[0047] C-2. Protective layer

[0048] Protective layers 12 and 13 are all formed by any suitable film that can be used as polaroid protective layer.As the material of the main component of film, specifically provide for example transparent resin, including cellulose-based resin such as triacetyl cellulose (TAC), and polyester-based resin, polyvinyl alcohol-based resin, polycarbonate-based resin, polyamide-based resin, polyimide-based resin, polyethersulfone-based resin, polysulfone-based resin, polystyrene-based resin, polynorbornene-based resin, polyolefin-based resin, (methyl) acrylic resin and acetate-based resin.Also provide for example thermosetting resin or UV curable resin, for example (methyl) acrylic resin, carbamate-based resin, (methyl) acrylic acid carbamate-based resin, epoxy resin and silicone-based resin.Also provide for example glassy polymer, for example siloxane-based polymer.In addition, can use the polymer film described in Japanese Patent Application Laid-Open No. 2001-343529 (WO01 / 37007A1). For example, a resin composition containing a thermoplastic resin having a substituted or unsubstituted imide group on its side chain and a thermoplastic resin having a substituted or unsubstituted phenyl and nitrile group on its side chain can be used as the material of the film, and the composition is, for example, a resin composition containing an alternating copolymer formed of isobutylene and N-methylmaleimide and an acrylonitrile-styrene copolymer. The polymer film can be, for example, an extrudate of the resin composition.

[0049] In at least one embodiment of the present invention, protective layer can all be formed by using (meth) acrylic resin. (Meth) acrylic resin with lactone ring structure is particularly preferably used as (meth) acrylic resin, because this resin has high heat resistance, high transparency and high mechanical strength. The example of (meth) acrylic resin with lactone ring structure is included in, for example, Japanese Patent Application Laid-Open No. 2000-230016, Japanese Patent Application Laid-Open No. 2001-151814, Japanese Patent Application Laid-Open No. 2002-120326, Japanese Patent Application Laid-Open No. 2002-254544 and Japanese Patent Application Laid-Open No. 2005-146084, all with (meth) acrylic resin of lactone ring structure, and its description is incorporated herein by reference.

[0050] Among the protective layers 12 and 13, the protective layer arranged outside the head-up display device (e.g., the protective layer 12 of the illustrated embodiment) may have any suitable surface treatment layer. The surface treatment is, for example, a surface treatment such as: a hard coating treatment; an anti-reflection treatment; an anti-sticking treatment; an anti-glare treatment; or a treatment for improving heat insulation properties, such as a flame retardant treatment or an infrared absorption treatment.

[0051] The thickness of each of the protective layers is preferably 10 μm to 50 μm, more preferably 10 μm to 30 μm. When the dust cover is surface-treated, the thickness of the outer protective layer (protective layer 12) is the thickness including the thickness of its surface-treated layer.

[0052] C-3. Other layers

[0053] The polarizing plate 10 may also include any suitable other layers. The other layers are, for example, retardation layers. Any suitable retardation layer may be used as the retardation layer. When the polarizing plate further includes a retardation layer, any suitable number, type, arrangement, etc. may be used as the number, type, arrangement, etc. of the retardation layer. In at least one embodiment of the present invention, the retardation layer is a λ / 4 plate. In at least one embodiment of the present invention, the in-plane retardation Re(550) of the retardation layer is preferably 3,000nm or greater. Such a retardation layer may be arranged on the outside of a head-up display device using a dust cover (i.e., on the side opposite to the side where the display, etc., is stored). When the in-plane retardation of the retardation layer falls within the above range, even when its retardation changes according to the viewing angle, the retardation of the entire retardation layer is large enough to reduce the impact on the visibility of the head-up display device. As a result, excellent visibility can be achieved even when the display screen is viewed through a pair of polarized sunglasses. The term "Re(λ)" as used herein refers to the in-plane retardation of the film measured at 23°C with light having a wavelength of λnm. Therefore, the term "Re (550)" refers to the in-plane retardation of the film measured with light having a wavelength of 550 nm at 23° C. When the thickness of the film is represented by "d" (nm), Re (λ) is determined by the equation "Re = (nx-ny) × d", where "nx" represents the refractive index in the direction in which the refractive index in the plane of the film becomes maximum (i.e., the slow axis direction), and "ny" represents the refractive index in the direction perpendicular to the slow axis in the plane (i.e., the fast axis direction).

[0054] D. Pressure-sensitive adhesive layer

[0055] The pressure-sensitive adhesive layer 30 and 30' can be formed by using any suitable pressure-sensitive adhesive. Specific examples of pressure-sensitive adhesives for forming pressure-sensitive adhesive layers include acrylic pressure-sensitive adhesives, rubber-based pressure-sensitive adhesives, silicone-based pressure-sensitive adhesives, polyester-based pressure-sensitive adhesives, urethane-based pressure-sensitive adhesives, epoxy-based pressure-sensitive adhesives, and polyether-based pressure-sensitive adhesives. According to the purpose, the pressure-sensitive adhesive with the desired characteristics can be prepared by adjusting the type, quantity, combination and blending of monomers such as the base resin for forming the pressure-sensitive adhesive, as well as the blending amount, reaction temperature and reaction time of the cross-linking agent. The base resin of the pressure-sensitive adhesive can be used alone or in combination. From the viewpoint of transparency, processability and durability, acrylic pressure-sensitive adhesives are preferred. The details of the pressure-sensitive adhesive for forming the pressure-sensitive adhesive layer are described in, for example, Japanese Patent Application Laid-Open No. 2016-155981, and its description is incorporated herein by reference. The thickness of the pressure-sensitive adhesive layer can be, for example, 10 μm to 100 μm.

[0056] E. Head-up display

[0057] A head-up display device according to at least one embodiment of the present invention includes: a display configured to emit projection light; at least one reflector configured to reflect the projection light; and the above-mentioned dust cover. Figure 2 is a schematic cross-sectional view of a head-up display device according to at least one embodiment of the present invention. The head-up display device of the illustrated embodiment includes: a display 40 configured to emit projection light; reflectors 50 and 60 configured to reflect the projection light; a housing 70 in which the display 40 and the reflectors 50 and 60 are stored; and a dust cover 100 covering an opening portion of the housing 70. Although the head-up display device of the illustrated embodiment includes two reflectors, the number of reflectors may be one.

[0058] In the illustrated embodiment, the projection light emitted from the display 40 is reflected by the reflectors 50 and 60. When the head-up display device is a vehicle-mounted head-up display device, the projection light reflected by the reflector is projected onto the windshield 200, and the projected image can be seen. As can be seen from the illustrated embodiment, the head-up display device has an opening portion, so sunlight can be applied from the opening portion to the inside of the head-up display device to damage a portion of the housing, such as a display. As described above, a head-up display device according to at least one embodiment of the present invention can use a dust cover including an iodine-based polarizer as a dust cover. When the dust cover includes a polarizer, sunlight can be suppressed from being incident (transmitted) into the head-up display device. The polarization degree of the iodine-based polarizer is higher than the polarization degree of any other polarizer, such as a dye-based polarizer, and therefore can exhibit high heat insulation properties. As a result, the durability of the head-up display device can be further improved. In addition, the polyene formation of the polarizer is suppressed, so the image display performance of the device can be maintained.

[0059] Any suitable configuration may be adopted as the display 40. The display is typically, for example, a liquid crystal display device. The liquid crystal display device includes a polarizing plate, so the projection light emitted from the liquid crystal display device may be linearly polarized light.

[0060] Any suitable configuration can be adopted as each of the reflectors 50 and 60. The reflectors 50 and 60 each have, for example, a mirror portion and a mirror frame, which is configured to hold the mirror portion at a predetermined position in the housing 70. The mirror portion can be a plane mirror, or can be a concave mirror. In the illustrated embodiment, a plane mirror and a concave mirror are respectively adopted as the reflector 50 and the reflector 60. The use of a concave mirror enables the video to be projected to be magnified and displayed. The radius of curvature of the concave mirror can be appropriately set according to, for example, the purpose and the size of the video to be projected. When the reflector 50 is arranged, the reflector 50 can be, for example, a plane mirror (cold light mirror) configured to transmit only infrared rays and reflect visible rays and UV light.

[0061] The housing 70 is a box-shaped member having an internal space capable of storing the display 40 and the reflectors 50 and 60. The housing 70 generally has an opening portion, and the projection light emitted from the display 40 through the opening portion is emitted to the outside of the housing 70. The housing 70 may include any suitable material. When the head-up display device is a vehicle-mounted head-up display device, a preferred constituent material of the housing 70 is, for example, a material that hardly experiences a temperature rise due to sunlight exposure and is easy to form. Specific examples of such materials include acrylic resins, epoxy resins, polyester-based resins, urethane-based resins, polyolefin-based resins, fluorine-based resins, and phenoxy resins. The housing 70 may be incorporated into a part of the automobile, or may be a member independent of the automobile. For example, the dashboard of the automobile may be used as the housing.

[0062] Example

[0063] The present invention is specifically described below by way of examples. However, the present invention is not limited to these examples. The measuring methods of the characteristics are as follows. Unless otherwise specified, the terms "parts" and "%" in the examples and comparative examples are by weight.

[0064] (1) Thickness

[0065] Thicknesses of 10 μm or less were measured with an interferometer thickness gauge (manufactured by Otsuka Electronics Co., Ltd., product name: “MCPD-3000”). Thicknesses exceeding 10 μm were measured with a digital micrometer (manufactured by Anritsu Corporation, product name: “KC-351C”).

[0066] (2) Polyene formation

[0067] The single-layer transmittance of the sample before and after the heating test was measured, and the change in the single-layer transmittance ΔTs was calculated by the following equation. The single-layer transmittance was measured with a spectrophotometer (manufactured by Murakami Color Research Laboratory Co., Ltd., product name: "DOT-3") according to JIS Z 8701. The heating test was performed by cutting the dust cover obtained in each of the examples and comparative examples into a size of 4.0 cm long × 4.0 cm wide to provide a sample; and placing the sample under conditions of 105°C for 1,000 hours.

[0068] ΔTs=Ts–Ts0

[0069] In this equation, Ts0 represents the single-layer transmittance of the sample before heating, and Ts represents the single-layer transmittance of the sample after heating.

[0070] The case where the change ΔTs was a negative value was evaluated as “polyene formation present (NG, single layer transmittance decreased)”, and the case where the single layer transmittance after heating was equal to or greater than the single layer transmittance before heating was evaluated as “polyene formation absent”.

[0071] (3) Warping

[0072] The warpage of the sample before and after the heating test was measured, and the change in warpage ΔC was calculated by the following equation. The warpage was measured with a steel linear scale (scaled in increments of 0.5 mm) while the sample was placed on a flat plate. The heating test was performed by the following steps: the dust cover obtained in each of the embodiments and comparative examples was cut into a size of 25 cm long × 350 cm wide to provide a sample; and the sample was placed under conditions of 105°C for 1,000 hours. When warpage was present, each of the samples was placed on a flat plate so that the warpage was upward (so that the sample had a concave shape). The dimension in the vertical direction between the horizontal surface of the flat plate and the edge of each side of the sample was measured with a linear scale, and the maximum value was defined as the warpage of the sample.

[0073] ΔC=C(mm)–C0(mm)

[0074] In this equation, C0 represents the warpage (mm) of the sample before heating, and C represents the warpage (mm) of the sample after heating.

[0075] A sample having a ΔC of ±15 mm or more, or a sample having an end portion bent to be placed inwardly with respect to an inflection point of warpage was evaluated as “warpage present (NG)”.

[0076] (4) Moisture permeability

[0077] According to JIS Z 0208, the moisture permeability of the support plate was measured under the conditions of a temperature of 40° C. and a humidity of 92% RH.

[0078] (5) Tensile elastic modulus

[0079] According to JIS K 7161, the tensile elastic modulus of the support plate is measured under the conditions of a temperature of 23° C.±2° C. and a humidity of 50% RH±10% RH.

[0080] (6) Iodine content

[0081] The fluorescence X-ray intensity (kcps) corresponding to iodine was measured with a fluorescence X-ray analyzer (manufactured by Rigaku Corporation, product name: "ZSX-PRIMUS IV"). The peak value of the fluorescence X-ray spectrum was used as the fluorescence X-ray intensity (kcps). By using the fluorescence X-ray intensity per unit thickness of the polarizer thus obtained, the iodine content was calculated by the following equation.

[0082] (iodine content (weight %)) = 14.474 × (fluorescent X-ray intensity per unit thickness of polarizer) (kcps)

[0083] (7) Thermal insulation properties

[0084] A 21 cm high container having an opening portion (measuring 26.0 cm×17.5 cm) in the upper portion is considered to be a head-up display device. A thermocouple (manufactured by Chino Corporation, product name: "COVERED THERMOCOUPLEVT6") is loaded into the container, and the dust cover obtained in each of the embodiments and comparative examples is placed in the opening portion. Next, light emitted by a xenon lamp of a single-light source type solar simulator (manufactured by Yamashita Denso Corporation, product name: "YSS-180S-HS1K") is applied from a position 30 cm above the opening portion for 3 minutes, and the temperature rise of the thermocouple in the device is measured. The test was carried out under the conditions of 23°C±2°C and a humidity of 50% RH±15% RH. A temperature rise of 25°C or less means that the dust cover has excellent heat insulation properties.

[0085] (8)Polarization degree

[0086] The transmittance (single-layer transmittance) of the polarizing plate (alone) was measured using a spectrophotometer (manufactured by Murakami Color Research Laboratory Co., Ltd., product name: "DOT-3"). In addition, the transmittance when two polarizing plates of the same kind are superimposed on each other so that the transmission axes of the two polarizing plates are parallel to each other (parallel transmittance: H0), and the transmittance when the polarizing plates are superimposed on each other so that the transmission axes of the two polarizing plates are perpendicular to each other (cross transmittance: H0) were measured using the same spectrophotometer. 90 Then, by combining the parallel transmittance (H0) and the cross transmittance (H 90 ) is applied to the following equation to calculate the polarization degree of the polarizer.

[0087] Polarization degree (%) = {(H0 – H 90 ) / (H0+H 90 )} 1 / 2 ×100

[0088] Single layer transmittance, parallel transmittance (H0) and cross transmittance (H 90 ) are all Y values ​​for visibility calibration using the second-degree viewing field (C light source) of JIS Z8701.

[0089] [Production Example 1] Production of Pressure-Sensitive Adhesive Sheet

[0090] 1. Preparation of pressure-sensitive adhesive

[0091] 100 parts by weight of toluene, 60 parts by weight of dicyclopentyl methacrylate (DCPMA) (manufactured by Hitachi Chemical Co., Ltd., product name: "FA-513M"), 40 parts by weight of methyl methacrylate (MMA) and 3.5 parts by weight of chain transfer agent (α-thioglycerol (TGR)) were loaded into a four-necked flask. Then, under a nitrogen atmosphere, the mixture was stirred at 70°C for 1 hour. After that, 0.2 parts by weight of azobisisobutyronitrile was loaded into the flask as a thermal polymerization initiator, and the mixture was reacted at 70°C for 2 hours, and then at 80°C for 2 hours. After that, at a temperature of 130°C, the reaction liquid was loaded under the atmosphere, and toluene, chain transfer agent and unreacted monomers were removed by drying. Thus, a solid (meth) acrylic polymer was obtained. The glass transition temperature of the obtained (meth) acrylic polymer was 144°C and the weight average molecular weight was 4,300.

[0092] Separately, 67 parts by weight of 2-ethylhexyl acrylate (2EHA), 15 parts by weight of N-vinyl-2-pyrrolidone (NVP), 3 parts by weight of hydroxyethyl acrylate (HEA), 15 parts by weight of 4-hydroxybutyl acrylate (4-HBA), 0.05 parts by weight of photopolymerization initiator 1 (manufactured by Ciba Specialty Chemicals, product name: "IRGACURE 184"), and 0.05 parts by weight of photopolymerization initiator 2 (manufactured by Ciba Specialty Chemicals, product name: "IRGACURE651") were loaded into a four-necked flask. Then, the mixture was exposed to UV light under a nitrogen atmosphere for partial photopolymerization. Thus, a partially polymerized product (acrylic polymer syrup) having a polymerization rate of about 10% by weight was obtained.

[0093] 5 parts by weight of the above (meth)acrylic polymer, 0.04 parts by weight of trimethylolpropane triacrylate, and 0.3 parts by weight of γ-glycidoxypropyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., product name: "KBM-403") were added to 100 parts by weight of the obtained acrylic polymer syrup, and the materials were uniformly mixed to provide an acrylic pressure-sensitive adhesive composition.

[0094] 2. Production of pressure-sensitive adhesive sheets

[0095] One surface of a polyester film having a thickness of 38 μm (manufactured by Mitsubishi Chemical Polyester Film, product name: "MRF") was subjected to a peeling treatment with silicone. The above-mentioned acrylic pressure-sensitive adhesive composition was applied to the peeling-treated surface of the film so that its final thickness became 25 μm. Thus, an applied layer was formed. Next, one surface of a polyester film having a thickness of 38 μm (manufactured by Mitsubishi Chemical Polyester Film, product name: "MRN") was subjected to a peeling treatment with silicone, and the surface of the applied acrylic pressure-sensitive adhesive composition was covered with the film so that the peeling-treated surface of the film was on the applied layer side. Thus, the applied layer (pressure-sensitive adhesive layer) of the acrylic pressure-sensitive adhesive composition was isolated from oxygen. Next, by using a black light lamp (manufactured by Toshiba Corporation), an illumination of 5 mW / cm 2 The obtained pressure-sensitive adhesive layer sheet was irradiated with UV light (measured with TOPCON UVR-T1 having a maximum sensitivity at about 350 nm) for 360 seconds. The gel fraction of the obtained pressure-sensitive adhesive layer was 82.4% by weight.

[0096] [Example 1]

[0097] (Polarizing film production)

[0098] A polyvinyl alcohol (PVA) film having an average degree of polymerization of 2,700 and a thickness of 45 μm was stretched and conveyed while being dyed between rollers having different peripheral speed ratios. First, the PVA film was stretched 1.2 times in its conveying direction while being swollen by immersing it in a water bath at 30°C for 1 minute. Next, the film was stretched 3 times in the conveying direction (relative to the unstretched film) while being dyed by immersing it in an aqueous solution (liquid temperature: 30°C) of potassium iodide (potassium iodide concentration: 0.03 wt%) and iodine (iodine concentration: 0.3 wt%) for 1 minute. Next, the stretched film was stretched 6 times in the conveying direction (relative to the unstretched film) while being immersed in an aqueous solution (bath) of boric acid (boric acid concentration: 4 wt%), potassium iodide (potassium iodide concentration: 5 wt%) and zinc sulfate (zinc sulfate concentration: 3.5 wt%) for 30 seconds. After stretching, the film was dried in an oven at 40° C. for 3 minutes to provide a polarizing plate having a thickness of 18.0 μm (iodine content: 3.1% by weight).

[0099] (Production of polarizing film laminates)

[0100] A polyvinyl alcohol resin containing acetoacetyl groups (average degree of polymerization: 1,200, saponification degree: 98.5 mol%, degree of acetoacetylation: 5 mol%) and an aqueous solution of methylol melamine in a weight ratio of 3:1 were used as adhesives. Under a temperature condition of 30°C, a transparent protective film (manufactured by Nitto Denko Corporation) having a thickness of 30 μm formed by a modified acrylic polymer having a lactone ring structure was bonded to one surface of the polarizer with an adhesive by using a roll bonding machine, and a triacetyl cellulose (TAC) base film (manufactured by FUJIFILM Corporation, product name: "TJ40UL", thickness: 40 μm) was bonded to the other surface thereof with an adhesive by using a machine. Next, the resulting laminate was heated and dried in a 70°C oven for 5 minutes so that the transparent protective film was bonded to both surfaces of the polarizer. The thickness of each layer in the adhesive layer was 0.03 μm to 1 μm.

[0101] Separately, 5 parts by weight of a photopolymerization initiator (manufactured by BASF SE, product name: "IRGACURE 906") and 0.01 parts by weight of a leveling agent (manufactured by DIC Corporation, product name: "GRANDIC PC 4100") were added to a resin solution, the resin solution being obtained by dissolving a UV curable resin monomer or oligomer containing urethane acrylate as a main component in butyl acetate, relative to the solid content in 100 parts by weight of a resin solution (manufactured by DIC Corporation, product name: "UNIDIC 17-806", solid content concentration: 80% by weight). Next, cyclopentanone (CPN) and propylene glycol monomethyl ether (PGM) were added at a ratio of 45:55 so that the solid content concentration in the resin solution became 36% by weight. Thus, a hard coating forming material was prepared. The resulting hard coating forming material was applied to a TAC base film so that the thickness of the hard coating after curing became 9 μm. Thus, a coating film was formed. Next, the coating film was dried at 90°C for 1 minute, and then a high-pressure mercury lamp was applied with a total light intensity of 300 mJ / cm 2 The coating film was cured by UV light to form a hard coating layer on the TAC base film. Thus, a polarizing plate having a configuration of "TAC base film (HC-TAC) with a hard coating layer formed thereon / polarizer / acrylic transparent protective film" was obtained.

[0102] Next, the pressure-sensitive adhesive layer of the pressure-sensitive adhesive sheet obtained in Production Example 1 is transferred to the HC-TAC side of the polarizing plate and the polycarbonate resin side of the support plate A (manufactured by Wavelock Advanced Technology Co., Ltd., product name: "ShineTech (trademark) AW-10SU", thickness: 200μm, polymethyl methacrylate (PMMA) resin layer thickness: 30μm, polycarbonate resin layer thickness: 170μm), and the HC-TACs are bonded to each other. Similarly, the pressure-sensitive adhesive layer is also transferred to the acrylic transparent protective film side of the polarizing plate, and the polycarbonate resin layer side of the support plate A and the acrylic transparent protective film are bonded to each other. Thus, a dust cover (surface resin layer (PMMA) / substrate (polycarbonate (PC) resin) / polarizer (Pol) / substrate (polycarbonate (PC) resin) / surface resin layer (PMMA)) is obtained. The obtained dust cover was evaluated as described above. The results are shown in Table 1.

[0103] [Example 2]

[0104] A dustproof cap was obtained in the same manner as in Example 1 except that a support plate B (manufactured by Wavelock Advanced Technology Co., Ltd., product name: "ShineTech (trademark) AW-10SU", thickness: 300 μm, PMMA resin layer thickness: 35 μm, polycarbonate resin layer thickness: 265 μm) was used instead of the support plate A. The obtained dustproof cap was subjected to the above-mentioned evaluation. The results are shown in Table 1.

[0105] [Example 3]

[0106] A dust cover was obtained in the same manner as in Example 1 except that a support plate C (manufactured by Wavelock Advanced Technology Co., Ltd., product name: "ShineTech (trademark) AW-10SU", thickness: 250 μm, PMMA resin layer thickness: 30 μm, polycarbonate resin layer thickness: 220 μm) was used as a support plate on the acrylic transparent protective film side of the polarizing plate. The obtained dust cover was subjected to the above-mentioned evaluation. The results are shown in Table 1.

[0107] [Example 4]

[0108] A dustproof cap was obtained in the same manner as in Example 1 except that a support plate D (polycarbonate resin film manufactured by Mitsubishi Gas Chemical Company, Inc., product name: “MRF08U (product category) D51 (product number)”, thickness: 300 μm) was used instead of support plate A. The results are shown in Table 1.

[0109] (Comparative Example 1)

[0110] Support plate E was obtained by applying a hard coat layer forming material to a polycarbonate resin film (manufactured by Mitsubishi Gas Chemical Company, Inc., product name: “MRF08U (product category) D51 (product number)”, thickness: 175 μm) in the same manner as in Example 1 so that its thickness after drying became 5 μm.

[0111] A dustproof cap was obtained in the same manner as in Example 1 except that the support plate E was used instead of the support plate A. The obtained dustproof cap was subjected to the above-mentioned evaluation. The results are shown in Table 1.

[0112] (Comparative Example 2)

[0113] Support plate F was obtained by applying a hard coat forming material to a polycarbonate resin film (manufactured by Mitsubishi Gas Chemical Company, Inc., product name: “MRF08U (product category) D51 (product number)”, thickness: 120 μm) in the same manner as in Example 1 so that its thickness after drying became 5 μm.

[0114] A dustproof cap was obtained in the same manner as in Example 1 except that the support plate F was used instead of the support plate A. The obtained dustproof cap was subjected to the above-mentioned evaluation. The results are shown in Table 1.

[0115] (Comparative Example 3)

[0116] A dust cover was obtained in the same manner as in Example 1 except that the support plate B was bonded to the acrylic transparent protective film side of the polarizing plate instead of the support plate A. The obtained dust cover was subjected to the above-mentioned evaluation. The results are shown in Table 1.

[0117] (Comparative Example 4)

[0118] (Polarizing Plate Production)

[0119] 0.017 parts by weight of CI Direct Orange 39, 0.022 parts by weight of CI Direct Blue 1, 0.012 parts by weight of CI Direct Violet 9 and 0.5 parts by weight of Glauber's salt were dissolved per 100 parts by weight of water to prepare a dye bath. The local maximum absorption wavelengths (λmax: under water) of the dyes used are as follows: CI Direct Orange 39: about 440 nm; CI Direct Blue 1: about 621 nm; CI Direct Violet 9: about 575 nm.

[0120] Separately, a film (thickness: 75 μm) formed of polyvinyl alcohol having a degree of polymerization of 2,400 was uniaxially stretched 6.1 times by wet stretching. The stretched film was immersed in warm water at 63°C and then immersed in the above-mentioned dyeing bath at 73°C for dyeing. Next, the dyed film was immersed in a 72°C aqueous solution formed by 100 parts by weight of water and 7.8 parts by weight of boric acid. Thereafter, the film was washed with water and dried to provide a polarizer (single-layer transmittance: 43.2%, polarization degree: 95.0%, thickness: 28 μm). A triacetyl cellulose film (manufactured by Fuji Photo Film Co., Ltd., thickness: 40 μm) was bonded to each of the two surfaces of the resulting polarizer to provide a polarizing plate.

[0121] A dust cap was obtained in the same manner as in Example 1 except that the obtained polarizing plate was used. The obtained dust cap was subjected to the above-mentioned evaluation. The results are shown in Table 1.

[0122] (Comparative Example 5)

[0123] A dustproof cap was obtained in the same manner as in Example 2 except that the polarizing plate used in Comparative Example 4 was used. The obtained dustproof cap was subjected to the above-mentioned evaluation. The results are shown in Table 1.

[0124] (Comparative Example 6)

[0125] Support plate A (manufactured by Wavelock Advanced Technology Co., Ltd., product name: "ShineTech (trademark) AW-10SU", thickness: 200 μm, polymethyl methacrylate (PMMA) resin layer thickness: 30 μm, polycarbonate resin layer thickness: 170 μm) was used alone and the above evaluation was performed. The results are shown in Table 1.

[0126]

[0127] [Evaluate]

[0128] As is apparent from Table 1, in each of the dust caps of the present examples, warping and polyene formation were suppressed. The use of an iodine-based polarizing plate as the polarizing plate further improved the heat shielding property.

[0129] The dust cover according to at least one embodiment of the present invention can be applied to a head-up display device, and can be more suitable for a vehicle-mounted head-up display device in such a device.

[0130] According to at least one embodiment of the present invention, it is possible to provide a dust cover in which warping is suppressed and which can suppress polyene formation of the polarizing plate even when an iodine-based polarizing plate is used.

Claims

1. Dust cover, which includes: a first support plate; A polarizing plate comprising an iodine-based polarizer; and The second support plate, The moisture permeability of at least one of the first support plate or the second support plate is 37 g / (m 2 24 hours) or greater, The thickness of at least one of the first support plate or the second support plate is 200 μm or more, The iodine-based polarizer has a center line L in the thickness direction thereof. P The center line L of the dust cover in the thickness direction D The distance between them is 20 μm or less.

2. Dust cover, which includes: a first support plate; A polarizing plate comprising an iodine-based polarizer; and The second support plate, The moisture permeability of at least one of the first support plate or the second support plate is 37 g / (m 2 24 hours) or greater, at least one of the first support plate or the second support plate has a tensile elastic modulus of 1,600 MPa or more measured at 23°C±2°C, The iodine-based polarizer has a center line L in the thickness direction thereof. P The center line L of the dust cover in the thickness direction D The distance between them is 20 μm or less. 3 . The dust cover according to claim 1 , wherein the support plates each comprise a base material and a surface resin layer. The dust cover according to claim 3 , wherein the base material comprises a polycarbonate resin.

5. The dust cover according to claim 3, wherein the surface resin layer contains polymethyl methacrylate. 6 . The dustproof cap according to claim 3 , wherein the surface resin layer has a thickness of 30 μm or more. 7 . The dust cover according to claim 1 , wherein the polarizer has an iodine content of 2.2 to 4.0 wt %.

8. A head-up display device, comprising: a display configured to emit projection light; at least one reflector configured to reflect the projection light; and A dust cover according to claim 1 or 2.

Citation Information

Patent Citations

  • Thermoplastic resin laminate

    JP2002254544A

  • Lactone ring-containing polymer, and its manufacturing method and application

    JP2005146084A

  • Transparent film

    WO2001037007A1

  • Polarizing member and head-up display device comprising same

    WO2017199916A1